Design, Simulation, and Optimization of Polarization-Independent Four-Port Optical Waveguide Circulator Based on a Ferrite Material - Babak Hashemi; Amir Hamid Alizadeh (International Journal of Optics)
Optical circulators are used in optical devices such as multiplexers, demultiplexers, and optical routers. Usually, the magnetic material in the center of the circulator conducts light by interacting with the electromagnetic wave. In this research, a polarization-independent four-port optical waveguide circulator with the presence of a rhombus-shaped ferrimagnetic material has been designed, simulated, and optimized in the three-dimensional part of Comsol software. This designed circulator unlike the previous structures has four ports which use the transmission matrix method to conduct waves. By selecting the appropriate size and type of central ferrite, as well as the scale of input and output channels, the most optimal situation is obtained for power transmission with less than 1 dB loss when port 1 is input and port 2 is output.